扶正化瘀方对非酒精性脂肪性肝病大鼠肝纤维化及ACE-Ang Ⅱ-AT1R轴的影响 - Miao-miao HUO; Bian-qiao, CHENG; Wei-guo, LIN; Xu-wei, WU (Jie fang jun yi xue za zhi, 2018)
Objective To evaluate the influence of Fuzhenghuayu decoction on fibrotic liver tissue and angiotensin- converting enzyme- angiotensin Ⅱ- angiotensin Ⅱ 1 receptor (ACE-Ang Ⅱ-AT1R) axis using a nonalcoholic fatty liver fibrosis rat model system. Methods Forty male Sprague-Dawley (SD) rats were randomly divided into the following groups: normal control group, liver fibrosis model group, and liver fibrosis model Fuzhenghuayu drug intervention at low-dose [0.75g/(kg.d)] group and high-dose [1.5g/(kg.d)] group. Except the normal control group, the other three groups were fed high-fat diet for 24 weeks to induce nonalcoholic hepatic fibrosis model. The drug intervention was administered via oral-gastric irrigation once daily for 6 times per week over a 6-week period. The rats were sacrificed at the end of 6 weeks for serum and liver tissue collection. The levels of serum total cholesterol (TC), triglycerides (TG), alanine aminotransferase (ALT), aspartate aminotransferase (AST) were measured by standard biochemical